Involving people with a lived experience when developing a proposal for Health Technology Assessment research of nonsurgical treatments for pelvic organ prolapse: Process and reflections - Eugenie Evelynne Johnson; Joanne Lally; Allison Farnworth; Fiona Pearson (Wiley, 2023)
Abstract Introduction Patient and public involvement (PPI) is an expectation when conducting research, including Health Technology Assessment (HTA), but practical guidance for those wishing to embed PPI into the grant application process is not always easily accessible. We wanted to ensure that PPI was central when preparing a proposal for an investigator‐led evidence synthesis HTA investigating nonsurgical interventions for pelvic organ prolapse (POP) in women. Here, we describe our methods. Methods We recruited two patient co‐applicants separately through an open process to help ensure that patient voice was present within our proposal's management and direction. We invited co‐applicants to attend research team meetings and comment on the full proposal. We designed, recruited to and facilitated a scoping workshop, as well as undertook its subsequent evaluation. The insight shared within the workshop for patients with a lived experience of POP, including our patient co‐applicants, helped us develop the scope and rationale behind our HTA proposal. We particularly considered the interventions to include within the evidence synthesis. We also considered the outcome measures for both the evidence synthesis and economic evaluation. We elicited ideas about where and how results could be disseminated. Feedback suggested the workshop was as valuable for the attendees as it was for the researchers, making them feel valued and listened to. The time spent by researchers working on the activity was substantial and not directly funded but a necessary and valuable activity in developing our potential HTA. Our work was informed using the UK Standards for Public Involvement and the Authors and Consumers Together Impacting on eVidencE (ACTIVE) framework. Conclusions PPI can be enormously valuable in both developing and strengthening research proposals. However, further guidance is needed to help researchers recognise the level and type of involvement to use at this early stage, particularly given the large time investment needed to embed meaningful PPI. Patient and Public Contribution Women with a lived experience of POP were involved at every stage of the grant application process; their involvement is documented in full throughout this work.